Autoantibodies against CD74 in spondyloarthritis. Issue 6 (17th May 2013) - Baerlecken, N T; Nothdorft, S; Stummvoll, G H; Sieper, J; Rudwaleit, M; Reuter, S; Matthias, T; Schmidt, R E; Witte, T
Abstract : Background: Spondyloarthritis (SpA) is a common debilitating inflammatory disorder. Establishing the diagnosis is often difficult, since abnormalities in conventional X-ray develop with a latency of several years and only HLA-B27 is used as a laboratory marker. The goal of our study was to identify new autoantibodies as diagnostic markers of SpA. Methods: Protein array technology was used to screen for new autoantigens in ankylosing spondylitis. Then, the results were confirmed by ELISA using Class II-associated invariant chain peptide domain of CD74 as antigen. Sera for the ELISA were obtained from 216 patients with axial (n=156) and peripheral (n=60) SpA. Sera of patients with psoriatic arthritis without axial involvement as another subtype of peripheral SpA, rheumatoid arthritis, systemic lupus erythematosus, HIV infection and blood donors served as controls. All donors provided informed consent for the study which was approved by the local ethics committee (project number 4928). Results: Using protein arrays, we detected IgG antibodies against CD74 in SpA sera. Using ELISA technology on sera that had previously been frozen for several years, IgG autoantibodies against CD74 were found in 67% of the SpA patients and were even more frequent in patients with a short disease duration. In the controls, the prevalence of the new autoantibodies was 18/40 (45%) in psoriatic arthritis without axial involvement, 9/80 (11%) in rheumatoid arthritis, 6/40 (15%) in systemic lupus erythematosus, 1/40 (2.5%) in HIV and 1/125 (0.8%) in blood donors. Conclusions: Antibodies against CD74 could provide an important additional tool for diagnosis of SpA.